Intentions to Use Vasectomy Contraception: Application of Theory Planned Behavior (Medico Legal Update, 2021)
In Indonesia, 8% of married men use a FP method, 3% use a modern FP method and 4% use a traditionalFP method/method. The percentage of married men who use condoms (3%) is higher than the percentagewho choose vasectomy (less than 1%). The study was conducted in the Madiun town administration usinga community-based cross-sectional study design. The town is found in East Java Province, Indonesia. Thetotal sample of this study is 323 married man with fixed disease sampling. The results showed that “attitude”(p=0.04) and “perceived behavioral control” (p=